Towards a balanced curriculum and fair assessment of students from different disciplines in an interdisciplinary science course. - Lo Svenningsen, Sine (Improving University Science Teaching and Learning, 2023)
The project aims to improve the course Biological Dynamics, which will be offered for the second time in block 4, 2011, based on the students’ evaluations from 2010 and my experiences from giving the course in 2010. I will focus on the main challenges we encountered in the course. One objective is to plan the curriculum and the teaching activities so that students, despite different educational backgrounds, feel both confident and challenged, and experience a positive learning climate. Another is to develop teaching activities which are aligned with the overall aim of the course, namely promoting interdisciplinarity and equipping students with a common language with which to discuss topics that cover multiple disciplines. Finally, I will discuss the challenge of assessing the course participants fairly, so that students from all backgrounds have an equal opportunity to do well in the course provided they put in the effort.